Movimento anarquista no Brasil: uma análise das contribuições políticas durante a Primeira República - SOUZA, Jocenildo Teixeira de (UNIFAP – Universidade Federal do Amapá, 2022)
This research had the intention to investigate, historiographically, the anarchist movement in Brazil during the First Republic, it is apparent there are shortages on the subject, this fact is not without reason, since for many anarchism decades was obscured and almost extinguished history in the country. The rescue of the anarchist currents memory, especially the anarchosyndicalism, their influence has been task to few researchers, which is why the literature on the subject is still in its infancy. Through this research, it sought to that end, the unveiling in what areas and spheres of society influenced; their outstanding contributions, making a historical overview, from reading articles and books that could achieve the proposed objectives: to highlight the contributions of the anarchist movement in Brazil during the First Republic; analyze how and why the contributions of anarchist movements have been relegated to the margins of Brazilian history. This study was of qualitative nature, especially the use of the historical method, based on the analysis of literature sources and articles scoped highlight the contributions of the anarchist movements in Brazil, assuming that the official history of Brazil had and still has intended to hide the achievements of the anarchist movement that was significant in that period.